Amino acid digestibility of high-protein corn dried distillers grains with solubles in pigs - Jacela, J.Y.; Frobose, H.L.; DeRouchey, Joel M.; Tokach, Michael D.; Nelssen, Jim L.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
The objective of this experiment was to determine the digestibility of amino acids (AA) in a high-protein dried distillers grains with solubles (DDGS) product. Six growing barrows (initially 50 lb) were surgically fitted with a T-cannula at the terminal ileum to allow for ileal digesta collection. After recovery, the pigs were randomly allotted to 2 dietary treatments in a crossover design with 2 periods. The first diet contained high-protein DDGS (67% of the diet) as the sole protein source; the second was a nitrogen-free diet for determining basal endogenous AA loss. Chromic oxide was added to both diets as an indigestible marker. Ileal digesta samples were collected each period and analyzed for AA concentration. Standardized and apparent ileal digestibilities (SID and AID, respectively) of AA were calculated after chemical analysis of the high-protein DDGS, diets, digesta, and fecal samples. Nutrient composition analysis of the high-protein DDGS showed a CP value of 36.5%, crude fat of 4.8%, and phosphorous content of 0.38%. The AID for lysine, methionine, threonine, and tryptophan were 65.9, 87.0, 72.8, and 76.2%, respectively. Values for SID AA were calculated to be 67.8, 87.5, 75.0, and 78.6% for lysine, methionine, threonine, and tryptophan, respectively. In conclusion, this high-protein DDGS product has greater AA digestibility values than traditional DDGS. Therefore, this product appears well-suited for use in swine diets but needs further evaluation to determine its effects on pig growth performance.
Keywords: Amino acids; Digestibility; Dried distillers grains with solubles; Swine